Influence of Operational Agility on Employees' Performance in Pharmaceutical Industries in Kwara State - Moriam Adeyemi Aremu; Risikat Bola Sulaiman; Taiye Hassan Ahmed (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2025)
Poor operational agility has been recognised as a factor affecting employees' performance. Adequate technological infrastructures, innovative capabilities, and digital transformation systems are reported to enhance workers' performance. This study examined the influence of operational agility on employees’ performance. A descriptive survey was used. The population was 435 staff of Tuyil Pharmaceutical, Ilorin. The sample was 208 employees, calculated using Taro Yamane's formula for sample size determination. A structured